El río y la ciudad (2020)
This project takes a series of thoughts about perception and sensorial experience towards an urban intervention strategy in the Eje Ambiental of Bogotá, which accommodates singular spaces between the street tiles that aim to unveil before pedestrians and inhabitants how fragile reality is, and the chaotic way in which the palimpsestic build of the city has made us used to paradox, turning nature into a mirage. Space talks trough it?s materiality, which flows and transforms constantly due to the natural forces that keep the dynamic equilibrium, opening in the surface, windows to the past. A gap, glimpses to the layers which support our reality. A tile, a fix, another layer of meaning that tells the story of a domesticated nature. Five tiles pretend to enrich and make dialogs between us, nature and city visible, and add to the narratives of a gap, those embodied in ceramics, worked carefully to be part of that space.